The Analysis of Figurative Language Used in The Lyric of Bruno Mars Album - Putri Raisah Sihotang; David Togi Hutahaean; Leonita Maria Efipanias Manihuruk; Tiarma Intan Marpaung; Basar Lolo Siahaan (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2024)
The objectives of this research are: (1) To find out the types of figurative language used in Bruno Mars’ song album. (2) To find out the most dominant type of figurative language used in Bruno Mars’ song album. The design of this research is descriptive qualitative research. The type of data for this research is Bruno Mars' songs from the album 24K Magic, namely 24K Magic, That's What I Like, Calling All My Lovelies, Chunky, Versace on the Floor, Finesse, Perm, Straight Up & Down, Too Good to Say Goodbye. In this research, the researchers used Keraf's theory. From the analysis, the results of this research show that the total data of types of figurative language used in the album 24K Magic by Bruno Mars is 32 (100%). The most dominant figurative language style is Eponym. There are 11 (34%) Eponym in the song lyrics, 6 (19%) total personification data, 10 (31%) total metaphor data, and 5 (16%) similes in the song lyrics. The presence of figurative language in songs makes the conveyed message more interesting for the listeners. The author suggests that other researchers continue to analyze figurative language as it can help readers understand the meaning contained in the song lyrics. Another suggestion is for researchers who want to analyze figurative language in song lyrics to use other objects such as novels, films, poetry, etc.